Indoor Air Quality and Sick Building Syndrome: Are Green Buildings Better than Conventional Buildings? - Gawande, Sonal (Indian J Occup Environ Med, 2020)
Indoor air quality (IAQ) influences human health, productivity and wellness. Green buildings are believed to have better IAQ. The 'sick building syndrome' (SBS) describes a set of nonspecific symptoms experienced by occupants due to time spent in a building with poor IAQ. Thus this study was undertaken to assess the IAQ in green buildings and compare it with that of conventional buildings. The prevalence of SBS in both types of buildings is also studied. In five pairs of green and conventional buildings measurements of comfort parameters (temperature & relative humidity) and indoor air pollutants using monitors was done. 148 employees which included 84 from green buildings and 64 from conventional buildings were surveyed for SBS using an interviewer-administered questionnaire. The analysis was done using SPSS16 and included Mann Whitney for IAQ pollutant concentrations and Chi-square for the SBS prevalence. Similar indoor air quality was found in both types of buildings. The mean of temperature, CO2 and formaldehyde was statistically lower in green buildings. The SBS prevalence was found to be 38.1% in green buildings and 53.1% in conventional buildings. Thus to conclude the poorly maintained green building does not have any added advantage for occurrence of SBS.